Update on immunomodulatory drugs (IMiDs) in hematologic and solid malignancies - Vallet, Sonia; Witzens-Harig, Mathias; Jäger, Dirk; Podar, Klaus (Expert opinion on pharmacotherapy, 2012)
Introduction: Thalidomide and its analogs [small molecule immunomodulatory drugs (IMiDs®)] are among the most successful new therapeutic agents of recent years. Thalidomide is now an integral part of multiple myeloma (MM) therapy. Lenalidomide has been approved for the treatment of patients with relapsed MM and 5q-myelodysplastic syndromes (MDS). Currently, more than 400 clinical trials are evaluating the activity of lenalidomide, alone or in combination with other conventional or novel therapies, in newly diagnosed MM and 5q-MDS. Based on their broad range of actions within the tumor microenvironment, IMiDs are currently also evaluated in a wide variety of additional hematologic and solid malignancies. Areas covered: This paper reviews the historic development of thalidomide and its derivatives and presents novel insights into their mode of action. Moreover, it discusses up-to-date clinical trials investigating IMiDs and potential future research and therapeutic perspectives in MM and other malignancies. Expert opinion: Although IMiDs have emerged as powerful agents for the treatment of hematologic and solid tumors, more preclinical and clinical studies are urgently needed both to increase our knowledge of their mechanisms of action, and to optimize their clinical use, in order to further improve the patient's quality of life and survival.